Si Miao San Attenuates Inflammation and Oxidative Stress in Rats with CIA via the Modulation of the Nrf2/ARE/PTEN Pathway. (11th February 2021) - Shen, Pan; Huang, Yao; Ba, Xin; Lin, Weiji; Qin, Kai; Wang, Hui; Du, Maotao; Haung, Ying; Wang, Yu; Chen, Zhe; Tu, Shenghao
Abstract : Objective . Si Miao San (SMS) is a traditional Chinese formula used in China to treat rheumatic diseases. To date, its mechanism in rheumatoid arthritis (RA) treatment is uncertain. Our study aims to assess the antiarthritic effects of SMS in experimental arthritic rats. Materials and Methods . SMS (8.63, 4.31, and 2.16 g/kg/day) was orally administered after the first immunization from day 14 to day 53. The effects of SMS on rats with collagen-induced arthritis (CIA) were evaluated by arthritis score and histological assessment. The levels of cytokines and anti-CII antibodies in rat serum were measured by ELISAs. The expression of oxidative stress parameters was detected by biochemical assay kits. The levels of Nrf2, HO-1, NQO1, and PTEN were determined by western blotting. Results . Medium- and high-dose SMS treatment significantly decreased arthritis scores and alleviated ankle joint histopathology in the rats with CIA. It inhibited the production of IL-6, TNF- α, COX-2, and PGE2 in rat serum. SMS also suppressed the expression of anti-CII antibodies IgG1 and IgG2a. Moreover, SMS significantly suppressed the levels of MDA and MPO in the synovial tissues while increasing the levels of SOD and CAT in the rats with CIA. The levels of Nrf2, HO-1, NQO1, and PTEN were upregulated by SMS in rat synovial tissues. Conclusions . This study demonstrated that SMS effectively alleviated the disease progression of CIA by decreasing the levels of proinflammatory cytokines and reducing oxidative stress damage, as indicated by IL-6, TNF- α, COX-2, and PGE2 levels; inhibiting the overproduction of MDA and MPO; and enhancing antioxidant enzymes by upregulating the Nrf2/ARE/PTEN signalling pathway.